Cardiovascular toxic effects of antitumor agents: Pathogenetic mechanisms. Issue 213 (May 2022) - Pantazi, Despoina; Tselepis, Alexandros D.
Abstract: Cancer treatment is associated with various side effects of antitumor agents, which increase the morbidity and mortality of these patients. Cardiovascular complications are considered to be one of the most important side effect of the anticancer drugs. The antitumor drugs that express cardiovascular effects include anthracyclines, tyrosine kinase inhibitors, taxanes, fluoropyrimidines, alkylating agents, vascular endothelial growth factor inhibitors, immune checkpoint inhibitors, proteasome inhibitors and human epidermal growth receptor type 2 antibodies. The spectrum of cardiovascular effects of anticancer drugs is broad and include, among others, heart failure, arrhythmias such as atrial fibrillation and ventricular tachyarrhythmias, hypertension (systemic or pulmonary), cardiomyopathy, myocarditis, valve disease, pericardial disease, vascular events (arterial thrombosis, venous thromboembolism) and myocardial ischemia (acute coronary syndrome, angina). The molecular mechanisms by which anti-cancer therapies lead to cardiotoxicity are diverse and vary according to the specific type of agent used. They include oxidative stress, topoisomerase 2-β inhibition in cardiomyocytes, inflammation, endothelial dysfunction, apoptosis, disruption of Ca2+ homeostasis, mitochondrial dysfunction, DNA damage, increase in various circulating microRNAs levels, alterations in the function of voltage-gated potassium channels. The management of cardiovascular complications in cancer patients is a new challenge for oncologists and cardiologists. Thus the cardio-oncology field has developed the last decade in order to precisely predict and efficiently treat the cancer treatment-related cardiovascular diseases. Highlights: Cardiovascular complications are considered to be one of the most important side effect of the anticancer drugs. Anticancer treatments can cause cardiovascular complication with various underlying molecular mechanisms. The management of the cardiovascular complications in cancer patients is a new challenge for oncologists and cardiologists.